Adenosine causes transient dilatation of coronary arteries in man. - Watt, A H (1987)
We investigated the effects of i.v. adenosine on coronary blood flow in 10 normal subjects undergoing investigation for chest pain. Coronary flow transiently doubled after greater than or equal to 3.5 mg adenosine without increase in perfusion pressure, systolic load or inotropic state at a constant, paced heart rate. The data provide direct evidence that adenosine dilates coronary arteries in man. The transience of the effect suggests a possible role for adenosine in repeated estimations of coronary flow reserve.